MENINGKATKAN KEMAMPUAN MENGENAL HURUF VOCAL MELALUI METODE JARIKUBACA BAGI ANAK TUNAGRAHITA RINGAN KELAS II di SLB N MANGGIS GANTING BUKITTINGGI - Tri Olivia Oktaviani (Universitas Negeri Padang, 2015)
The background of this research background by mild mental retardation found child class II in SLB N Manggis Ganting Bukittinggi. Problems found were children unable to recognize letter vocals. While the curriculum the child is able to read simple sentences, but after an assessment conducted children's ability to recognize vowel in can be 20%.Where children are only able to mention, show and write a letter. Based on the researchers aim to prove whether jarikubaca method can improve the ability of a vowel to the child. This type of research is the single subject research (SSR), with ABA design and analysis of research data using visual analysis chart.Analysis of the data showed that baseline (A1) performed five times with a mean level of 25%, the percentage of 100% stability tendency towards stable (=). continued intervention (B) for eight times the mean level of 80.20%, the percentage of stability 12.5%, a trend toward increased (+). Further baseline condition (A2) is performed five times with a mean level of 91.66%, the percentage of 0% stability tendency towards increased (+). There is also the inter-state analysis of the data obtained changes in condition B / A1 is +25, and A2 / B is +25. Overlape on data analysis B / A 0% and B / A2 12.5%. Thus the research hypothesis is accepted jarikubaca method can improve the ability to know the vowel for mild mental retardation children in SLB class II N Manggis Ganting Bukittinggi. Keyword : Letter vocals, mild mental retardation; jarikubaca method